The Effects of Inorganic Nitrogen form and CO2 Concentration on Wheat Yield and Nutrient Accumulation and Distribution - Carlisle, Eli; Myers, Samuel S.; Raboy, Victor; Bloom, Arnold J. (Frontiers in Plant Science, 2012)
Nitrogen (N) is the most limiting nutrient for plant growth and primary productivity. Inorganic N is available to plants from the soil as ammonium (NH4+) and nitrate (NO3–). We studied how wheat grown hydroponically to senescence in controlled environmental chambers is affected by N form (NH4+ vs. NO3–) and CO2 concentration (‘subambient’, ‘ambient’, and ‘elevated’) in terms of biomass, yield, and nutrient accumulation and partitioning. NH4+-grown wheat had the strongest response to CO2 concentration. Plants exposed to subambient and ambient CO2 concentrations typically had the greatest biomass and nutrient accumulation under both N forms. In general NH4+ plants had higher concentrations of total N, P, K, S, Ca, Zn, Fe, and Cu, while NO3– plants had higher concentrations of Mg, B, Mn, and NO3–-N. NH4+ plants contained amounts of phytate similar to NO3– plants but had higher bioavailable Zn, which could have ramifications for human health. NH4+ plants allocated more nutrients and biomass to aboveground tissues whereas NO3– plants allocated more nutrients to the roots. The two inorganic nitrogen forms influenced plant growth and nutrient status so distinctly that they should be treated separately. Moreover, plant growth and nutrient status varied in a non-linear manner with atmospheric CO2 concentration.